Theory-based team diagnostics and interventions - Ohlert, J.; Zepp, C. (Sport and exercise psychology research: From theory to practice, 2016)
Various sports teams conduct team interventions throughout the season. In most cases, however, the effect of these interventions is only very small. Within this abstract, we argue in favor of a theory-based methodology when planning and conducting team diagnostics and interventions: (1) getting an overview of those group processes or team factors with theoretical and empirical relevance for team performance; (2) selecting valid instruments for a team diagnostics; (3) conducting the team diagnostic to detect factors that are in need of improvement; (4) based on the results of the diagnostics, selecting intervention methods that show empirical evidence regarding a specific effect on the respective factors, and that can easily be implemented into daily training; (5) conducting the intervention with a duration of several weeks; and (6) evaluating the effects of the intervention. The different steps of this methodology as well as perspectives and limitations are discussed. (übern.)